The explananda in North Germanic Tonogenesis - Riad, Tomas (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2025)
The article discusses two explananda relating to tonogenesis in North Germanic: A) the origin of a tonal representation, B) the origin of a lexical distinction. Tradition has largely focused on B before A. I elucidate the assumptions of B > A hypothesis and argue that it fails to properly address the phonologization of lexical tones. The alternative hypothesis, A > B, primarily looks to account for the phonologization of lexical tone (i.e., A). The mechanism assumed is the same as is active today: reduction of secondary stress in the word-internal clash context with attendant reanalysis of a postlexical tone as lexical. A prosodic post-lexical rule – present in all dialects today – assigns the word tone of accent 2, which subsequently becomes lexicalized in a morpheme by morpheme manner. The developments of a postposed definite article and epenthetic vowels, processes that are always mentioned as instrumental in demonstrating the lexical distinction (B) do not directly bear on tonogenesis as such. The result is that A is the first explanandum.